Assessment of the yam landraces (Dioscorea spp.) of DR Congo for reactions to pathological diseases, yield potential, and tuber quality characteristics - Adejumobi, I.I.; Agre, A.P.; Onautshu, O.D.; Adheka, J.G.; Cipriano, I.M.; Monzenga, J.C.L.; Komoy, J. (MDPI, 2022)
Yams (Dioscorea spp.) possess the potential to contribute to food security and poverty alleviation in DR Congo; however, yam production is limited by several constraints, including the lack of yam improvement programs to address challenges relating to yield improvement, resistance to foliar diseases, and post-harvest tuber quality. Identification of a superior genotype for these traits and reservoirs of genes for improvement would guide yams’ improvement. This study aims to evaluate and identify landraces with superior performance for farmers and consumers. We evaluated 191 accessions from six yam species, and significant variation in the performances was observed at p < 0.05. Accessions of D. alata were superior for tuber oxidative browning (−0.01), D. cayenensis for high yield potential (29 t/ha), D. bulbifera for yam mosaic virus (YMV) tolerance (AUDPC = 3.88), and D. rotundata for tuber dry matter content (37%). A high genotypic and phenotypic coefficient of variation (>40) was observed for tuber yield, number of tubers per plots, tuber flesh oxidative browning, and tuber flesh texture. High broad-sense heritability estimates (>60) were similarly observed for all the assessed parameters except number of tubers per plot. Tuber size was identified as the best predictor for tuber yield (b = 2.64, p < 0.001) and tuber dry matter content (b = 2.21, p < 0.001). The study identified twenty stable landrace accessions from three Dioscorea species (D. alata (7); D. cayenensis (2); D. rotundata (11)). These accessions combined high yield potential, high tuber dry matter, high tolerance to YMV and YAD, and low tuber flesh oxidation. The accessions could be considered for the establishment of a yam improvement program in DR Congo.